Koordinasi Dinas Pemberdayaan Perempuan Perlindungan Anak Pemberdayaan Masyarakat Pengendalian Penduduk dan Keluarga Berencana (DP3APMP2KB) dalam Penanggulangan Kekerasan Terhadap Anak di Kota Medan - Wan Nilovar Hauro Insiyyah; Asima Yanty Sylvania Siahaan (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The coordinating role of the Medan City Women's Empowerment, Child Protection, Community Empowerment, Population Control, and Family Planning Office (DP3APMP2KB) is crucial in efforts to address violence against children. Cross-sector coordination involving the police, hospitals, UPTD PPA, P2TP2A, and psychological and legal assistance institutions is key to ensuring that case handling is swift, integrated, and responsive to the victims' needs. This study used a descriptive qualitative method with data collection techniques through observation, in-depth interviews, literature studies, and document analysis. The study was conducted at the Medan City DP3APMP2KB office with informants consisting of the Head of UPTD PPA, the Women's and Children's Rights Protection Division, the Banit PPA Polrestabes, the PPA Task Force, and the community. The results of the study indicate that coordination between DP3APMP2KB and the police has been running quite well, especially in aspects of unity of action, division of labor, and discipline. However, the communication aspect is still not optimal due to obstacles in the delivery of information and the absence of a regular communication forum between agencies. This situation has resulted in less than optimal integration of case handling in the field. Therefore, strengthening communication mechanisms and ongoing coordination forums is necessary to improve the effectiveness of child protection in Medan City.